The protective and pathogenic role of Th17 cell plasticity and function in the tumor microenvironment - Pan, Yuanyuan; Yang, Wenjing; Tang, Bo; Wang, Xiaobo; Zhang, Qi; Li, Weiping; Li, Li (Frontiers in Immunology, 2023)
At the turn of the century, researchers discovered a unique subtype of T helper cells that secretes IL-17 and defined it as Th17. The latest study found that Th17 cells play both positive and negative definitive roles in the regulation of antitumor immune responses. Although the function of Th17 in the tumor microenvironment remains poorly understood, more and more studies have shown that this paradoxical dual role is closely related to the plasticity of Th17 cells in recent decades. Further understanding of the characteristics of Th17 cells in the tumor microenvironment could yield novel and useful therapeutic approaches to treat cancer. In this review, we further present the high plasticity of Th17 cells and the function of Th17-producing IL-17 in tumor immunity.